THE WAY OF IMPROVEMENT OF QUALITY OF THE JOINT WELDS RADIOGRAPHIC CONTROL - D. V. Dovnar; I. L. Zaharov (Литьë и металлургия)
The method allowing to increase the possibility of the defects recognition in the tasks of nondestructive check is described. The method can be used for processing of data and projecting of the nondestructive check systems.